1984
DOI: 10.1152/jn.1984.51.3.467
|View full text |Cite
|
Sign up to set email alerts
|

Primate raphe- and reticulospinal neurons: effects of stimulation in periaqueductal gray or VPLc thalamic nucleus

Abstract: Recordings were made from 132 raphe- and reticulospinal tract neurons in the medial part of the lower brain stem in 32 anesthetized monkeys. Recording sites were in the nucleus raphe magnus, the rostral nucleus raphe obscurus, and the reticular formation adjacent to the raphe. The neurons were identified by antidromic activation from the upper lumbar spinal cord. Of the population sampled, 83 cells were activated antidromically from the left dorsal lateral funiculus (DLF), 32 from the right DLF, and 17 from bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…However, no significant change in LCGU was detected in the spinal dorsal horn, nucleus raphe magnus and nucleus raphe dorsalis. Gerhart et al 7 demonstrated that, in monkeys, the latency for VB stimulation induced inhibition of dorsal horn neurons in the lumbosacral enlargement is 33.7 ms. Willis et al 19 , working with monkeys also, showed that the latency for VB stimulation excitation of RVM neurons is 35.6 ms and that the latency for antidromic activation of RVM neurons by stimulation of the DLF in an upper lumbar level is 8.2 ms. One can easily see, contrarily to what would be expected from Tsubokawa's hypothesis, that the latency for inhibition of dorsal horn neurons by VB stimulation is less than the sum of the latencies for VB stimulation excitation of RVM neurons and DLF stimulation antidromic excitation of RVM neurons.…”
Section: Commentsmentioning
confidence: 99%
“…However, no significant change in LCGU was detected in the spinal dorsal horn, nucleus raphe magnus and nucleus raphe dorsalis. Gerhart et al 7 demonstrated that, in monkeys, the latency for VB stimulation induced inhibition of dorsal horn neurons in the lumbosacral enlargement is 33.7 ms. Willis et al 19 , working with monkeys also, showed that the latency for VB stimulation excitation of RVM neurons is 35.6 ms and that the latency for antidromic activation of RVM neurons by stimulation of the DLF in an upper lumbar level is 8.2 ms. One can easily see, contrarily to what would be expected from Tsubokawa's hypothesis, that the latency for inhibition of dorsal horn neurons by VB stimulation is less than the sum of the latencies for VB stimulation excitation of RVM neurons and DLF stimulation antidromic excitation of RVM neurons.…”
Section: Commentsmentioning
confidence: 99%
“…First, anatomical studies reveal a heavy projection from the PAG (particularly its dorsal and ventrolateral aspects) to the RVM, as well as a projection from the RVM to the PAG (Gallagher and Pert, 1978;Abols and Basbaum, 198 1;Beitz, 1982a;Mantyh, 1982a;Carlton et al, 1983). Second, activation of PAG neurons, either by electrical stimulation or by microinjection of the potent neuroexcitant glutamate, has an excitatory effect on neurons in RVM (Fields and Anderson, 1978;Behbehani and Fields, 1979;Pomeroy and Behbehani, 1979;Mohrland and Gebhart, 1980;Vanegas et al, 1984b;Willis et al, 1984). Microinjection of opiates in the PAG also alters the activity of RVM neurons (Behbehani and Pomeroy, 1978;Mohrland and Gebhart, 1980;Cheng et al, 1986).…”
mentioning
confidence: 99%
“…Besides, there is also experimental evidence against the discussed hypothesis: A) Benabid et al 6 were not able to demonstrate any inhibition of DH nociceptive neurons following VB stimulation; the number of DH cells tested (8 cells), however, was too small, B) Aiko et al 2 , using the deoxyglucose method, could not detect any significant change in local glucose utilization in the nucleus raphe magnus and in the spinal dorsal horn following VB stimulation and C) The latency for VB induced inhibition of DH nociceptive neurons -33.7 ms n ' 2 7 is less than the sum of the latencies for VB induced excitation of RVM neurons -35.6 ms 27 - 29 and DLF antidromic excitation of RVM neurons -8.2 ms 27 -29 .…”
Section: Vb Stimulation Produces Pain Relief By Antidromic Activationmentioning
confidence: 93%
“…The mechanism of pain relief induced by VB stimulation, however, is still unknown. Many hypotheses have been proposed 1,2,6 ' 11 ' 16 ' 23 " 25,29 . Unfortunately, none of them seems to completely explain this mechanism.…”
mentioning
confidence: 99%